Gitelman syndrome, a rare condition: three clinical cases and pathophysiology review - Meireles, Daniel (2021)
Introduction: Gitelman syndrome (GS) is a renal tubular disorder characterized by hypokalemia, metabolic alkalosis, hypomagnesemia, and hypocalciuria. Clinical manifestations are nonspecific. Herein are reported three cases of GS with different age of onset, clinical manifestations, and management. Case Reports: Case 1 was a sixteen-year-old female, while Cases 2 and 3 presented at an atypical age (seven and eight years). Clinical manifestations mainly consisted of abdominal pain with vomits, together with past history of muscular weakness in Case 1. Diagnosis was based on usual electrolyte abnormalities, such as metabolic alkalosis with hypokalemia. Genetic diagnosis was confirmed in Case 3. Patients were treated with oral potassium, magnesium, and spironolactone, with symptom and electrolytic profile improvement. Discussion/Conclusions: GS is a rare condition that should be considered in cases of metabolic alkalosis and hypokalemia and all pediatricians should be aware of. Diagnosis is established based on biochemical profile and treatment response.